Hiányzó láncszemek Szenci Molnár Albert zsoltárköltőnk életművében - Fekete, Csaba (Studia Litteraria, 2026)
Personal remembrance of the author of the present study is characterised first, concerning some persons of the 20th century authorities of the Hungarian psalm and tune editors. It is now certain that the immediate source of the 1607 Hungarian edition was the 1598 German edition, rather than the French of 1562. At least some of these Psalms and editions must have been earlier known among Hungarian ministers in the second half of the 16th century, those who studied at German and Swiss universities. The study also describes some characteristics of the Psalms in the 1948 Hungarian edition. Characterised and compared are also a few examples of additional hymns to the 150 Psalms since the beginnings, that follow the examples of the German forerunners, i. e. the Decalogus, Pater noster and Magnificat in Hungarian verses.